#TITLE_ALTERNATIVE# - JUNAIDI (NIM 20506007), EKA
Runner turbine is one of the important components at Hydro Electric Power Plan (HEPP). The component was made from alloy of Cu-37Zn and always contacts mechanically with water, therefore it was potentially corroded. The quality of the operating water has an important role on corrosion process, particularly when it contains aggressively corrosive ions such as chloride and sulfide ions and the corrosion rate would be accelerated by increasing temperature. An effort to prevent of the corrosion can be performed by mean of inhibitor corrosion addition into the operating water. We were studied the rate of corrosion of runner turbine material under various concentration of chloride, sulfide ion and temperature. An artificial solution was made by referring to sample water quality of HEPP Saguling. We also investigated benzotriazole and cysteine as inhibitor. The rates of corrosion Cu-37Zn in absence and presence of the corrosion inhibitor were determined by using Electrochemical Impedance Spectroscopy (EIS) technique. Meanwhile by using Scanning Electron Microscopy (SEM) to observe surface morphology changed. The obtained results were indicated that the most corrosive environment was referred to water quality at HEPP Saguling with composition of 5.3 ppm Ca(NO3)2, 78 ppm NaCl and 15 ppm sulfide ion. The inhibitor efficiency of benzotriazole (80 ppm) and cysteine (25 ppm) at room temperature were 40.74% and 68.16% respectively. The increase of temperature from 25ÃƒÂ‚Ã‚Â°C to 55ÃƒÂ‚Ã‚Â°C was cause decreasing on inhibition efficiency of both inhibitor to 21.20% for benzotriazole (80 ppm) and 17.00% for cysteine (25 ppm). Since both inhibitors were physicaly adsorbed on Cu-37Zn with adsorption free energy (ΔGads) of benzotriazole and cysteine is ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â– 18.53 kJ/mol and ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â– 23.03 kJ/mol respectively.